Dual inhibition of BET and EP300 has antitumor activity in undifferentiated pleomorphic sarcomas and synergizes with ferroptosis induction - Stéphanie Verbeke; Aurélien Bourdon; Mathilde Lafon; Vanessa Chaire; Bertolo Frederic; Amina Naït Eldjoudi; Marie-Alix Derieppe; Francis Giles; Antoine Italiano (Translational Oncology)
Undifferentiated pleomorphic sarcoma (UPS) is the most frequent and the most aggressive sarcoma subtype for which therapeutic options are limited. The identification of new therapeutic strategies is therefore an important medical need. Epigenetic modifiers has been extensively investigated in recent years leading to the development of novel therapeutic agents. Dual BET/EP300 inhibitors have shown synergistic antitumor activity and have recently entered clinical development. To date, no data related to potential of BET/EP300 inhibition as a treatment in UPS have been reported. To investigate the therapeutic potential of BET/EP300 inhibition, we evaluated the antitumor activity of three compounds in vitro via MTT, apoptosis and cell cycle assays. The most potent inhibitor was evaluated in vivo in two animal models and the mechanisms of action were investigated by RNA sequencing, Western blotting and immunofluorescence staining. A CRISPR knockout screen was performed to identify resistance mechanisms. Among the three compounds tested, the dual inhibitor NEO2734 was the most potent, decreased the viability of UPS cells in vitro through a regulation of E2F targets and cell cycle and decreased the tumor growth in vivo. Moreover, we identified GPX4 as a gene involved in resistance and showed synergy between BET inhibition and ferroptosis induction.The present study demonstrated that dual BET/EP300 inhibitors have a relevant antitumor activity in a subgroup of UPS characterized by expression of MYC-targets pathway and identified a potent combination therapeutic strategy that deserves further investigation in the clinical setting.